Improving online learning through student stress evaluation - Sarvia, Elty; Wirawan, Christina; Kristianti, Meilena; Ramadhani, Zukhruf (OPSI, 2024)
The COVID-19 pandemic impacted almost all countries and caused disruptions in education. Governments, including Indonesia, closed schools and campuses to mitigate the spread of COVID-19, leading to a transition to online learning. This lasted for two years and continued with hybrid learning. The abrupt change increased stress, especially for already stressed students. This study assessed stress levels during online learning at the Industrial Engineering Study Programme of Maranatha Christian University, Bandung. Stress was measured subjectively using the Perceived Stress Scale (PSS) and objectively using Galvanic Skin Response (GSR) and pulse sensors on thirty-two students. The PSS results classified the stress perception of most students as ‘normal’ or ‘moderate’. Meanwhile, the results of the GSR and pulse sensor measurements indicated that the students were stressed. Furthermore, a comparison of stress levels between synchronous and asynchronous learning and between mathematics and theory courses was conducted. According to the findings, there was a difference in the average heart rate values between synchronous and asynchronous learning. There was also a difference between mathematics and theory courses. With this research, it is necessary to pay attention to learning methods, materials, etc. need to be designed to reduce student stress and improve student performance.